Программные средства для конечно-элементного моделирования двумерных задач теории ползучести - Бреславский, Дмитрий Васильевич; Корытко, Юлия Николаевна; Лысак, П. М. (НТУ "ХПИ", 2007)
The paper describes the program codes has been developed in NTU 'KhPI' for the numerical simulation of two-dimensional problems of creep theory, such as plane stress, plane strain and generalized stress-strain state. The Finite Element Method (FEM) jointly with multi step time integration methods are used as a method of computer simulation. The software structure, as well as verification of numerical results are discussed.
Keywords: машиностроительные конструкции; высокотемпературная ползучесть; двумерные задачи; программные продукты; длительная прочность; моделирование ползучести